Population Dynamics and World-Systems Analysis - Danna, Daniela (Journal of world-systems research, 2014)
World-systems analysis has given scant attention to population dynamics. Overlooked are large-scale macrohistorical population trends and their microhistorical foundation on procreative decisions-decisions which are taken by a historically changing subject of procreation: local elders or other authorities, head(s) of the household, couples, and women. The discipline of demography is also not as helpful as it could be, given its basis in modernization theory, which fails to recognize intentionality in reproduction in pre-capitalist societies. It assumes a model of 'demographic transition' from a state of 'natural fertility' to a state of conscious family planning, while also treating mortality as independent of fertility. Marxism recognized the importance of population as a source of labor for profit and capital accumulation. With its tools Sydney Coontz developed a demand for labor theory explaining in particular the decrease in the birth rate in England and the United States at the turn of the century. This theory was further developed by anthropologists of the 'mode of production and population patterns' who, with other authors, offer useful theories and insights to advance world-historical research on population. This article explores connections between population dynamics and world-systems analysis. I explore six key questions at different levels of analysis, including: 1) Are there world-systems' imperatives concerning human reproduction?; 2) Do human reproduction imperatives differ across world-systems?; 3) How do the (eventual) system 's requirements get transmitted to households and individuals?; 4) Why do people have children?; 5) Who is the subject of procreation decisions? ; and 6) How is the number of offspring chosen? Finally, I offer guidelines for applying the six questions to the capitalist world-economy. Adapted from the source document.